2023
DOI: 10.3390/app13052906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacterial Sealing Ability of Two Different Bio-Ceramic Sealers in Single-Rooted Teeth Using Single Cone Obturation Technique: An In Vitro Study

Abstract: The long-term success of root canal treatment requires the prevention of bacterial leakage between canal walls and root canal obturation. In this study, we compared the leakage of Enterococcus faecalis in thirty single-rooted mandibular premolars divided into three groups. The roots in two experimental groups were obturated using a single-cone obturation technique with two different bio-ceramic sealers (MTA Fillapex and CeraSeal) while the roots in the conventional group were obturated using the lateral conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This finding aligns with our descriptive CLSM images analysis. Furthermore, the antibacterial properties of calcium silicate sealers may contribute to the elimination of any remaining microorganisms [ 43 ], thereby potentially enhancing the success rate of root end treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with our descriptive CLSM images analysis. Furthermore, the antibacterial properties of calcium silicate sealers may contribute to the elimination of any remaining microorganisms [ 43 ], thereby potentially enhancing the success rate of root end treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AH Plus (Dentsply) sealer was chosen for its renowned ease of handling, sealability, and favorable biological performance in endodontic procedures [ 8 ]. The micro-retention of radicular dentin by AH Plus (Dentsply) contributes to enhanced adhesion to obturating materials compared to other sealers [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a polysaccharide that naturally occurs, and because it is non-toxic, biocompatible, ecological, and bioadhesive in nature, it has attracted interest in dentistry research [5][6][7] Among the many sealants used for root canal treatment, AH Plus (Dentsply Sirona, NC, USA) sealant has gained popularity due to its ability to improve dentin wettability, and gutta-percha sealability with adequate biological performance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The MTA-BCS have received scientific interest due to their superior properties in comparison to other sealers. Previous studies showed variations in properties of different commercially available MTA-BCS which might affect quality and durability (9)(10)(11) . The aim of the current study was to evaluate 3 commercially available MTA-BCS sealers regarding flow, film thickness and setting time.…”
Section: Introductionmentioning
confidence: 99%